Mitochondrial genome study of Camellia oleifera revealed the tandem conserved gene cluster of nad5–nads in evolution - Gu, Yiyang; Yang, Liying; Zhou, Junqin; Xiao, Zhun; Lu, Mengqi; Zeng, Yanling; Tan, Xiaofeng (Frontiers in Plant Science, 2024)
Camellia oleifera is a kind of high-quality oil supply species. Its seeds contains rich unsaturated fatty acids and antioxidant active ingredients, which is a kind of high-quality edible oil. As a hexaploid species with complex structure, its evolutionary rules has not been fully analyzed. So based on the second-generation sequencing data of C. oleifera, a 709,596 bp circular map of C. oleifera mitochondrial (mt) genome was found for the first time. And A total of 74 genes were annotated in the whole genome. Mt genomes of C. oleifera and three Theaceae species had regions with high similarity, including gene composition and gene sequence. At the same time, 5 conserved gene pairs were found in 20 species. And in all of the mt genomes, most of nad genes existed in tandem pairs. In addition, the species classification result which according to the gene differences in tandem with nad5 genes was consistent with the phylogenetic tree. These initial results provide a valuable basis for the further researches of Camellia oleifera, and a reference for the systematic evolution of plant mt genomes.